Pharmaceutical messianism and the politics of COVID-19 in the United States - Gideon Lasco; Vincen Gregory Yu; Nishtha Bharti (Taylor & Francis Group, 2024)
ABSTRACTThroughout the COVID-19 pandemic, public officials in the United States - from the President to governors, mayors, lawmakers, and even school district commissioners - touted unproven treatments for COVID-19 alongside, and sometimes as opposed to, mask and vaccine mandates. Utilising the framework of 'pharmaceutical messianism', our article focuses on three such cures - hydroxychloroquine, ivermectin, and monoclonal antibodies - to explore how pharmaceuticals were mobilised within politicised pandemic discourses. Using the states of Utah, Texas, and Florida as illustrative examples, we make the case for paying attention to pharmaceutical messianism at the subnational and local levels, which can very well determine pandemic responses and outcomes in contexts such as the US where subnational governments have wide autonomy. Moreover, we argue that aside from the affordability of the treatments being studied and the heterodox knowledge claiming their efficacy, the widespread uptake of these cures was also informed by popular medical (including immunological) knowledge, pre-existing attitudes toward 'orthodox' measures like vaccines and masks, and mistrust toward authorities and institutions identified with the 'medical establishment'. Taken together, our case studies affirm the recurrent nature of pharmaceutical messianism in times of health crises - while also refining the concept and exposing its limitations.